MODEL TINGKAT KEMISKINAN DI KABUPATEN BANGLI DENGAN PENDEKATAN PARTIAL LEAST SQUARE - ARTINI, NI WAYAN EKA SURYA; KENCANA, I PUTU EKA NILA; JAYANEGARA, KETUT (E-Jurnal Matematika, 2017)
The purpose of this research is to determine the dominant factors that influence the increment of poverty in 6 villages in Bangli regency which categorized as disadvantaged village in Bali province, namely, Binyan Village, Ulian Village, Langgahan Village, Abuan Village, Mengani Village, and Tembuku Village. The total respondents in this research are 84 poor families which determined through the stratified proportional random sampling method. The research regarding the poverty in disadvantaged village involves 5 latent variables, namely, poverty rate, inability to meet basic needs, the shortage of human resource competencies, inability to meet support needs, and the shortage of access to infrastructure which are each 5 of the latent variable have the reflective indicator. This research is using the variant-based (PLS-SEM) Structural Equation Modeling (SEM) method and calculated through smart PLS software. Based on the output of structural poverty rate equation model resulting from the analysis, it can be concluded that the increment of inability to meet basic needs, the shortage of human resource competencies, and the shortage of access to infrastructure have a significant effect towards the increment of poverty rate in a disadvantage village, meanwhile inability to meet support needs rate has no effect towards poverty rate in the disadvantaged village of Bangli Regency.